Electromagnetic Radiation From A Relativistic Jet Induced By A Plane Gravitational Wave - Epp, V.; Osetrin, K.; Osetrina, E.
Electromagnetic radiation of a relativistic gas or plasma jet in the field of a plane gravitational wave is investigated. The gravitational wave is considered as a weak (linearized) field on flat Minkowski spacetime. Исследовано электромагнитное излучение релятивистской газовой или плазменной струи в поле плоской гравитационной волны. Гравитационная волна рассматривается как слабое (линеаризованное) поле на плоском пространствевремени Минковского.
Keywords: Astrophysics